Ring-necked pheasant population and space use response to landscapes including spring cover crops - Godar, Alixandra Janelle (Kansas State University, 2020)
Planting spring cover crops as part of a crop rotation is a potential management practice to increase nesting and brood-rearing habitat for grassland birds in agricultural landscapes. Managers consider spring cover crops beneficial for wildlife populations while providing agricultural benefits by converting fallow fields to green fields during the breeding season. Populations of ring-necked pheasants (Phasianus colchicus) are declining in Kansas, USA primarily due to intensification of row-crop agriculture reducing availability of quality habitat. Use of spring cover crops may increase recruitment of ring-necked pheasants by providing nesting and brood-rearing habitats when the field would normally be fallow. Plant composition of spring cover crop seed mixes varies based on the relative amount of small grains, grasses, and forbs. To maximize the influence of cover crops on local wildlife, an understanding of how wildlife species use landscapes containing cover crops and the potential role of cover crops on population growth is required. My objectives were to (1) estimate the effect of spring cover crops on ring-necked pheasant population demography, (2) measure brood habitat and resource selection, (3) measure hen habitat and resource selection during the breeding season, and (4) test vegetation and insect composition among cover crop mixes and across other cover types. I compared ring-necked pheasant, plant, and insect response among three cover crop seed mixes and chemical fallow control treatments in 26 study sites on private land in four counties in western Kansas during 2017-2019. The three cover crop mixes were GreenSpring© (73 kg/ha; cool-season peas [Pisum sativum] and oats [Avena sativa]; 321.4 ha), Chick Magnet© (28 kg/ha; warm-season, broad-leafed forbs; 322.8 ha), and a Custom Wildlife Mix (41 kg/ha; multispecies mix for wildlife; 334.6 ha). In Conservation Reserve Program (CRP) fields within 2 km of treatments fields, I captured pheasants via nightlighting. Captured female pheasants (n = 139) were outfitted with a 15-g necklace-style very-high-frequency transmitter with an 8-hr mortality switch and a unique numbered aluminum leg band. Radio-collared individuals were monitored a minimum of twice a week from capture through September each year to measure movements and habitat use through nesting, brood rearing, and brood break-up periods. When conditions allowed, nesting females were monitored daily to determine nest success and nest hatch day. I conducted weekly vegetation surveys and biweekly insect sweep surveys in cover crop fields and surrounding potential habitat patches (i.e., CRP, native pasture, wheat, and other crop fields). I estimated home ranges for hens with ≥30 locations during the breeding season ( = 91.05 ha, SE = 14.43, n = 55). Selection of cover types was based on use versus availability of different cover types within each home range. Every location was assigned a cover type and 2 weekly locations were randomly selected for vegetation and insect surveys with a paired random location. I found that (1) pheasant population growth increased in cover crop fields, (2) broods used cover crop fields, (3) pheasants selected for CRP cover types across all time periods, but resource selection varied based on availability of resources and physiological requirements, and (4) cover crop fields provided more cover and insects than chemical fallow fields. Insect (Wilks λ = 0.07, F₅₃₆₇ = 18.66, P < 0.0001, n = 382) and vegetation measurements (Wilks λ = 0.15, F₅,₃₂₄₇ = 256.94, P < 0.0001, n = 3,316) varied by cover type. Chick Magnet provided the most forb cover of all cover types and the greatest average count of insects. Pheasant hens showed strong selection for CRP (2nd order: λ = 0.203, P = 0.001; 3rd order: λ = 0.204, P = 0.015). Broods used cover crops, crops fields, CRP, and grass. Cover crops comprised <5% of the landscape though it supported >25% of brood locations. Nest survival and hen survival estimates were lower than recommended for a stable population but pheasant hens with cover crops within their home range showed greater population growth than those without cover crops within their home range. Cover crops placed closely to CRP land may increase local pheasant population growth. Spring cover crops help mitigate the negative effects of intensive agriculture practices on grassland birds by providing additional insect forage and connecting isolated habitat patches during the breeding season.
Keywords: Ring-necked pheasant; Phasianus colchicus; Kansas; Cover crop; Survival; Nest